The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.drugpo.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of hepatitis C and treatment willingness amongst people who inject drugs in an era of direct acting antivirals

Abstract: Background Knowledge of hepatitis C virus (HCV) is believed to be important in altering risk behaviour, improving engagement in care, and promoting willingness to initiate HCV treatment. We assessed factors associated with HCV knowledge and treatment willingness amongst people who inject drugs (PWID) in an era of direct acting antivirals. Methods Data were derived from three prospective cohort studies of PWID in Vancouver, Canada, between June 2014 and May 2015. HCV knowledge and treatment willingness were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
2
26
1
1
Order By: Relevance
“…Many practitioners stated that they did not feel that offering it was appropriate in all stages of treatment and that a harm reduction kit was not appropriate for patients receiving DAA. In contrast, studies using a multipronged approach have, in fact, demonstrated successful treatment in PWID [35][36][37][38][39][40]. This signals a lack of knowledge among practitioners, which contributes to poorer health outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Many practitioners stated that they did not feel that offering it was appropriate in all stages of treatment and that a harm reduction kit was not appropriate for patients receiving DAA. In contrast, studies using a multipronged approach have, in fact, demonstrated successful treatment in PWID [35][36][37][38][39][40]. This signals a lack of knowledge among practitioners, which contributes to poorer health outcomes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly people who inject drugs [ 2 ] need to be addressed by customized concepts. A higher knowledge of HCV is associated with increased willingness for HCV treatment [ 37 ] and thus a general lack of awareness of HCV is still a major concern [ 38 ]. Moser et al [ 39 ] recently described a promising approach to address patients who are on opioid substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst PWID and other vulnerable populations, rapid testing has been shown to substantially increase coverage and referral rates . To date, many services have not been developed for vulnerable populations such as the homeless, PWID and prisoners, which must both contend with numerous social determinants that contribute to poor quality of life and poor social functioning as well as health inequalities . It should be emphasized that HCV treatment should be offered based on clinical rather than social factors or injecting‐related behaviours , underlining the necessity of overcoming obstacles to HCV treatment delivery to PWID.…”
Section: The Model Of Care (Moc): a Tool For Increasing Treatment Covmentioning
confidence: 99%